Evaluation of a nursing doctoral program from the perspective of Students, Alumni, and Faculty: A Quality-Oriented approach - Huda M. Atiyeh (18024367) (2023)
Aim This study aimed to evaluate the quality of the nursing doctoral program features as perceived by students, alumni, and faculty, and to test for significant differences among them. The study was guided by Wulff’s Alignment Model. Methods A cross-sectional design was used. Data were collected from 96 participants using an online survey, which utilized the program domain from the global, formative assessment measure - the Quality of Nursing Doctoral Education questionnaire. Results Overall, the faculty and alumni rated the program features more positively than the students. Significant differences were found in areas such as the program mission, research relevant issues, supportive learning environment, components of core courses, and post-doctoral issues. Conclusions Utilizing the formative assessment measure to evaluate the quality of nursing doctoral program features from the perspectives of students, alumni, and faculty highlighted areas of disagreement. The revealed information provides opportunities for improving the program's quality. Involving other stakeholders, such as program managers and decision-makers, would offer a more holistic view of the program's quality evaluation. Other Information Published in: International Journal of Africa Nursing Sciences License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijans.2023.100622